2018
DOI: 10.1038/s41598-018-30540-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Interaction between Plasma Characteristics and Liquid Properties in AC-driven Pin-to-Liquid Discharge

Abstract: This study investigated the mutual interaction between the plasma and plasma treated water (PTW). Many works have shown that the plasma treatment decreases the pH of PTW due to nitric oxide electrolyte ion but the interactions between PTW and the plasma are still largely unknown. We investigated the effect of PTW on a plasma as well as the effect of a plasma on PTW using a pin-to-liquid discharge system. It is found that PTW affects not only the chemical properties but also the physical properties of the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The concentration of the NO 3 and NO 2 in the PTW was 5.2 and 0.1 mg•L −1 , respectively, while the K + concentration was 5.0 mg•L −1 (P < 0.05) (Table 1). As previously reported, NO 3 and NO 2 can be formed in PTW through the dissolution of nitrogen oxides (NO, NO 2 , and N 2 O 3 ) formed near the electrodes when a high electric discharge is applied to air [22][23][24][25] . The dissolution of the nitrogen oxides in the water contributes to the low pH of the PTW, which can be explained by the reaction between NO 2 and 16 .…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The concentration of the NO 3 and NO 2 in the PTW was 5.2 and 0.1 mg•L −1 , respectively, while the K + concentration was 5.0 mg•L −1 (P < 0.05) (Table 1). As previously reported, NO 3 and NO 2 can be formed in PTW through the dissolution of nitrogen oxides (NO, NO 2 , and N 2 O 3 ) formed near the electrodes when a high electric discharge is applied to air [22][23][24][25] . The dissolution of the nitrogen oxides in the water contributes to the low pH of the PTW, which can be explained by the reaction between NO 2 and 16 .…”
Section: Resultsmentioning
confidence: 56%
“…Recent studies have reported that plasma technology is a promising tool for in-situ production of N-containing water in food and agriculture 16,21 . In an apparatus for plasma treatment, a high electric discharge produces N-containing ions in water through the dissolution of nitrogen oxides generated near the electrodes during air discharge [22][23][24][25] .…”
mentioning
confidence: 99%
“…the channel depth of the microfluidic device, is important in terms of breakdown voltage. With a small gap distance, lower breakdown voltage and higher discharge current is expected [55]. Hence decreasing the discharge gap from 100 to 50 µm, increases the power density in the discharge zone [56].…”
Section: Effect Of Channel Depthmentioning
confidence: 99%
“…These reactive species, including reactive oxygen species (ROS) and reactive nitrogen species (RNS) are responsible for the chemical and biological effects of PAW. Various setups have been used for PAW generation, including plasma jet (Hamdan, Profili, & Cha, 2020), dielectric barrier discharge (DBD; Jin et al., 2020), corona or spark discharge (Lu, Boehm, Bourke, & Cullen, 2017; Piskarev, 2019), pin/pins in water discharge, or plasma discharge in water with gas bubbles (Yoon et al., 2018).…”
Section: Introductionmentioning
confidence: 99%